od additive on female reproductive organs and hormones fo AzorubineEffects of in Sprague Dawley rat - Muhamad Amin, Faraidoon Abdul Sattar (The Iraqi Journal of Veterinary Medicine, 2019)
The objective of the present study was to assess the effects of various doses of Azorubine which is a food additive on the female reproductive organs in Sprague Dawley rats. Twenty four female Sprgue Dawley rats were divided randomly into 4 equal groups. Group 1(control group), group, 2, 3 and 4 were received Azorubine (5, 10 and 20 mg/kg) orally, daily for 30 days respectively. Blood samples were taken for estimation of white blood cells, red blood cells, hemoglobin and platelets, in addition Luteinizing, follicular stimulation, estrogen and progesterone hormones from the sera. The reproductive hormones levels affected drastically under the effects of different doses of treatment like Luteinizing hormone (0.69±0.25, 0.60±0.75 and 0.55±0.63), Follicular Stimulation hormone (0.17±0.11, 0.13±0.33 and 0.3±0.45), Progesterone hormone (0.50±0.77, 0.14±0.56 and 0.10±0.85), and estrogen hormone (0.45+0.43, 0.30±0.29 and 0.14±0.27) hormones were decreased significantly (P˂0.05) in groups of rats treated with each 5, 10 and 20 mg/kg doses of Azorubine respectively. Histopathologically, the ovaries treated with 5 mg/kg doses of Azorubine showing follicles at the beginning stages of growth with no Graffian follicle while the ovaries with 10 mg/kg doses of Azorubine contain fully grown Graffian follicles with no follicles at various stages as well as those with 20 mg/kg doses of treatment displaying no mature Graffian follicle with many atretic and shrunk follicles. The hematological outcomes are significantly affected by this food additive. The results of this work is concluded that Azorubine can be considered as one of the most important causes of infertility, hormonal disturbances and irregular estrus cycle in the female rat.